Capabilities of the electrochemical methods in the determination of narcotic and psychotropic drugs in forensic chemistry materials; Journal of Analytical Chemistry; Vol. 72, iss. 7 - Slepchenko G. B. Galina Borisovna (2017, 2017)
Title screen